2017
DOI: 10.3389/fpsyg.2016.01955
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Task-Specific Response Strategies in Blocked-Cyclic Naming

Abstract: In word retrieval, speakers need to select a lexical entry among several co-activated candidates for lexicalization. How a target entry is selected is a matter of ongoing debate. Semantic context effects on naming times, as seen in the blocked-cyclic naming paradigm, are of specific interest to this debate. In the standard version of this paradigm, participants name lists of objects compiled from several repetitions (cycles) of a small set of semantically related objects (homogeneous context) or unrelated obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 28 publications
(70 reference statements)
3
32
0
Order By: Relevance
“…We observed both the semantic blocking effect and the phonological facilitation effect: Reaction times (RTs) in the semantically homogeneous blocks were longer than those in the semantically heterogeneous blocks, in line with previous findings (e.g. Abdel Rahman & Melinger, 2009;Belke, 2017;Belke et al, 2005;Damian et al, 2001;Damian & Als, 2005). Furthermore, shorter RTs were observed in the phonologically homogeneous blocks relative to the phonologically heterogeneous blocks, which is in line with the phonological facilitation effect shown in previous studies (e.g.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We observed both the semantic blocking effect and the phonological facilitation effect: Reaction times (RTs) in the semantically homogeneous blocks were longer than those in the semantically heterogeneous blocks, in line with previous findings (e.g. Abdel Rahman & Melinger, 2009;Belke, 2017;Belke et al, 2005;Damian et al, 2001;Damian & Als, 2005). Furthermore, shorter RTs were observed in the phonologically homogeneous blocks relative to the phonologically heterogeneous blocks, which is in line with the phonological facilitation effect shown in previous studies (e.g.…”
Section: Discussionsupporting
confidence: 81%
“…The items in the homogeneous blocks are more predictable within the context of the task than items in the heterogeneous blocks (either semantically or phonologically). Alternatively, this component may correspond to a novel component related to task representation in the blocked cyclic naming paradigm, as argued by Belke and colleagues (Belke, 2008(Belke, , 2017Belke & Stielow, 2013). The component was proposed based on the observations that when participants have to perform a concurrent digit-retention task, their performances are affected in the blocked cyclic naming task, but not in the continuous naming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But there is disagreement about the origin of these opposing effects and how much they reflect underlying dynamics of the production system, as opposed to strategic effects. While facilitation has been viewed as a critical (Abdel Rahman & Melinger, 2009) or even the only real effect of co-activation of semantically related representations during the semantic-lexical activation phase (Mahon et al, 2007;Navarrete et al, 2014), others have viewed it as a strategic effect that is not consistently found (Belke, 2017;Belke et al, 2017). Collectively, the evidence suggests that while the facilitation often observed in the first cycle of the blocked cyclic naming task may be strategic in origin, facilitation observed in other cases is unlikely to be strategic (e.g., Nozari, 2019;Wei & Schnur, 2019), and is instead a reflection of the core dynamics of spreading activation in the system (see also Abdel Rahman & Melinger, 2009).…”
Section: Behavioral Consequences Of Naming Pictures In the Presence Omentioning
confidence: 99%
“…The studies presented here were not specifically designed to distinguish between temporary bias effects(Roelofs, 2018) or incremental or error-based learning accounts of CSI effects (e.g.,Belke, 2017;Howard et al, 2006;Oppenheim et al, 2010). Relatively short lags are used in both experiments.…”
mentioning
confidence: 99%